2017
DOI: 10.5152/tud.2017.35589
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and utilisation of preoperative multiparametric magnetic resonance imaging in robot-assisted radical prostatectomy: does it change the surgical dissection plan?

Abstract: Objective: We investigated the effect of the use of multiparametric prostate magnetic resonance imaging (mp-MRI) on the dissection plan of the neurovascular bundle and the oncological results of our patients who underwent robot-assisted radical prostatectomy. Material and methods:We prospectively evaluated 60 consecutive patients, including 30 patients who had (Group 1), and 30 patients who had not (Group 2) mp-MRI before robot-assisted radical prostatectomy. Based on the findings of mp-MRI, the dissection pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several authors studied the clinical value of preoperative MRI on surgical planning and PSM rates showing that it may influence the surgical decision in 26% to 59% of patients. [65][66][67][68][69][70] Recently, Kozikowski et al 71 reported, in their systematic review and meta-analysis, that MRI modified the NVB dissection on 1 or both sides in 35% of patients, of which 63% performed a more aggressive resection of the bundle and 37% had more preservation of the bundle. Furthermore, they showed that the appropriateness of the surgical decision modification based on the MRI findings was 77%.…”
Section: Mrimentioning
confidence: 99%
“…Several authors studied the clinical value of preoperative MRI on surgical planning and PSM rates showing that it may influence the surgical decision in 26% to 59% of patients. [65][66][67][68][69][70] Recently, Kozikowski et al 71 reported, in their systematic review and meta-analysis, that MRI modified the NVB dissection on 1 or both sides in 35% of patients, of which 63% performed a more aggressive resection of the bundle and 37% had more preservation of the bundle. Furthermore, they showed that the appropriateness of the surgical decision modification based on the MRI findings was 77%.…”
Section: Mrimentioning
confidence: 99%